As representações sociais dos agentes de controle de zoonoses sobre a dengue em Uberlândia, MG - Corrêa, Lourdes Maria Campos (2012)
Dengue is an infectious viral disease whose main vector is Aedes aegypti. A favorable environment for the vector, along with inefficient strategies to reduce their proliferation, allowed to the dengue virus the establishment and expansion of its circulation, increasing rates of the disease mainly in urban centers. The aim of this study was to identify the Social Representations of Agents Zoonosis Control of Uberlândia - MG, who deal directly with dengue, about dengue. This research is inside to a qualitative approach in the form of Social Representations. These are understood as theories and ways of thinking about a given phenomenon, which are structured collectively. However, starts from multiple interpretations of the individuality of your subjects. Semi-structured interviews were conducted with 20 agents of zoonoses active in dengue control from Center for Zoonosis Control of Uberlândia. The interviews were conducted between 5th and 22th October 2010, being recorded and later transcribed for analysis. The Term of Consent was applied before the interviews and the study was submitted to the Ethics Committee in Research of Universidade Federal Uberlândia. The agents exhibited representations close to scientific knowledge, as: is a serious disease, is an infectious disease, the vector is the female mosquito, the dengue mosquito has striped body, oviposition occurs on the surface of the vessels, the foci of larvae can be found in dirty water, there are four types of dengue virus, the disease treatment is done by hydration, a serological analysis is needed to establish the disease, the dengue mosquito is diurnal, the female mosquito uses the blood to the maturation of eggs, the oviposition occurs divided. RS different of scientific explanations also were found, such as dengue is a virus, the mosquito is not an animal. In the interviews, the agents presented representations relating to other aspects, including: the population is not committed to the prevention of dengue, the population is unaware of the seriousness of the problem, the media conveys outdated information, the agent job helps people to preventing dengue, training is positive, the population doesn\'t receive the agent; training conveys updated content, the population doesn\'t believe in dengue, dengue population thinks is God\'s thing, the population do bad treatments to the agent, prevention is sum of the individual and government, there should be punishments of fines, to solve the problem, lack the disclosure of the agent in the media, the campaigns should be more attractive, the agent job is nice, the training allows the exchange of experiences, the zoning helps the work of the agents. In comparison with the literature, we found that the representations of the agents are very close to scientific knowledge and probably have a positive effect on their practices, which are not limited to technical acts, but include an awareness and disclosure of information. We analyzed that these agents could be used as environmental educators, which would be furthered by his daily contact with the population.